2022
DOI: 10.1002/iju5.12525
|View full text |Cite
|
Sign up to set email alerts
|

Acute generalized exanthematous pustulosis during apalutamide treatment in a patient with prostate cancer

Abstract: Abbreviations & Acronyms AGEP = acute generalized exanthematous pustulosis DRESS = drug rash with eosinophilia and systemic symptoms HE = hematoxylin-eosin ICU = intensive care unit mCSPC = metastatic castration-sensitive prostate cancer mPSL = methylprednisolone TEN = toxic epidermal necrolysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Following a comprehensive literature review, we identified 9 reported cases of apalutamide-induced SCARs. These include five cases of TEN [ 4 7 ], one case of acute generalised exanthematous pustulosis [ 8 ], and 3 cases of DRESS (two with possible overlapping SJS) [ 9 , 10 ]. The median age of patients included in these cases is 83 years (range = 72–91 years).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Following a comprehensive literature review, we identified 9 reported cases of apalutamide-induced SCARs. These include five cases of TEN [ 4 7 ], one case of acute generalised exanthematous pustulosis [ 8 ], and 3 cases of DRESS (two with possible overlapping SJS) [ 9 , 10 ]. The median age of patients included in these cases is 83 years (range = 72–91 years).…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the basis of previous literature, dermatologic adverse events (dAEs) remain the most reported side effects of apalutamide. Up to now, 15 case reports and 3 retrospective analyses of apalutamiderelated drug eruptions have been published, with a divergent geographic distribution indicating the Japanese most vulnerable to dAEs of apalutamide (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). However, most of the dAEs remain mild and moderate with a fair prognosis (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Apalutamide is mainly responsible for benign maculo-papular exanthema (MPE), xerosis, lichenoid reactions [3][4][5]. But potentially life threating condition such as acute generalized exanthematous pustulosis [6], DRESS [7,8] or toxic epidermal necrolysis [3] have been described in the literature. We report two cases from our clinic illustrating the clinical spectrum of the CAE.…”
mentioning
confidence: 99%